PENGARUH LAYANAN KONTEN DENGAN MEDIA AUDIO VISUAL TERHADAP PENINGKATAN SELF AWARENESS REMAJA TENTANG BAHAYA SEKS PRA-NIKAH KELAS VII - Sitorus, Tania Hudba Salshabila; Nasution, Nani Barorah (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
This study aims to increase junior high school students' self-awareness regarding premarital sex through the application of audiovisual media content services. Using a pre-experimental research design, this study involved 32 seventh grade students at SMP Negeri 1 Air Batu. The results showed a significant increase in the mean score of students' self-awareness after participating in the intervention program, from 81.03 to 109.41. Data analysis using the Wilcoxon test showed a statistically significant difference between the pre-test and post-test scores. These results indicate that audiovisual media content services are effective in increasing students' self-awareness of premarital sex. Thus, this study provides empirical evidence regarding the potential use of audiovisual media as an adolescent sex education tool.